2022
DOI: 10.1371/journal.pmed.1003885
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pictorial health warnings on purchases of sugary drinks for children: A randomized controlled trial

Abstract: Background Pictorial warnings on tobacco products are promising for motivating behavior change, but few studies have examined pictorial warnings for sugary drinks, especially in naturalistic environments. This study aimed to examine the impact of pictorial warnings on parents’ purchases of sugary drinks for their children in a naturalistic store laboratory. Methods and findings Parents of children ages 2 to 12 (n = 325, 25% identifying as Black, 20% Hispanic) completed a shopping task in a naturalistic store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 44 publications
6
29
0
Order By: Relevance
“…Some options include restricting nutrient content claims or fruit imagery on products with high levels of added sugar, requiring FOP percentage juice content disclosures 19 (in addition to currently mandated back-of-pack disclosures 20 ), or requiring added-sugar warnings if these added sugars exceed a predetermined level. Evidence suggests that added-sugar warnings may reduce SSB purchases, [21][22][23][24][25] and the US Congress has introduced a bill to mandate such warnings. 26 Combining warnings with quantitative added-sugar disclosures (eg, teaspoons of added sugar/serving) may further discourage SSB consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Some options include restricting nutrient content claims or fruit imagery on products with high levels of added sugar, requiring FOP percentage juice content disclosures 19 (in addition to currently mandated back-of-pack disclosures 20 ), or requiring added-sugar warnings if these added sugars exceed a predetermined level. Evidence suggests that added-sugar warnings may reduce SSB purchases, [21][22][23][24][25] and the US Congress has introduced a bill to mandate such warnings. 26 Combining warnings with quantitative added-sugar disclosures (eg, teaspoons of added sugar/serving) may further discourage SSB consumption.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is having pictorial warnings on SSB containers to decrease the consumption of SSB. A recent study in North Carolina aimed to examine the impact of pictorial warnings based on parents' purchases of SSB for their children in a realistic store laboratory [10]. The study showed success in limiting parents' SSB purchases for their children by giving them a sense of feeling more in control of making healthier decisions [10].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in North Carolina aimed to examine the impact of pictorial warnings based on parents' purchases of SSB for their children in a realistic store laboratory [10]. The study showed success in limiting parents' SSB purchases for their children by giving them a sense of feeling more in control of making healthier decisions [10]. Another approach is for North Carolina to adopt more kids' meal policies like the nearly 24 states and localities that have already done so [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, labels were noted to have a greater effect on consumers’ understanding of sugar content than on the healthiness of choices. Recent findings suggest that graphical tobacco-style pictorial labels may be more effective than text- or icon-based warnings among parents [ 29 ] and young adults [ 21 ]. No jurisdictions currently require such pictorial warning labels, and the current study chose to focus on policy-relevant labels under consideration by the Australian government.…”
Section: Discussionmentioning
confidence: 99%